Atypical presentation of leiomyomas: A case series report - Mitra, Partha Sarathi; Kumari, Puja; Majhi, Dristy; Saha, Paramita; Saha, Amity; Mazumder, Ramakanta; Sanyal, Priyanka; Naskar, Tapan Kumar (Journal of Midwifery, 2025)
Fibroids are the most common benign smooth muscle tumours of uterus. Some patients are asymptomatic whereas symptomatic patients may present with heavy menstrual bleeding, dysmenorrhoea and pressure symptoms. Case report: Six Atypical fibroid cases have been reported in this case series report because of their rarity, diagnostic dilemma and difficulty in surgical approach supplemented by photographical evidence against each case. In case of Atypical fibroids, symptoms depend on the site of involvement and they may mimic other pelvic organ involvement like ovarian malignancy. Fibroids are mainly diagnosed by ultrasonography (USG) and magnetic resonance imaging (MRI) but may be difficult because of its unusual findings on USG and MRI. Patients can be managed either conservatively or surgically depending on their response. Surgical options include conservative surgery like Myomectomy or Hysterectomy, which can be done by open surgery or by minimally invasive surgery (MIS). The case series report may highlight on surgeons’ approach in case of atypical fibroids